PVC (polyvinyl chloride) coated yarn and preparation process thereof

By adding specific components to the PVC cladding layer and forming an intermediate layer between the core wire and the cladding layer, the shortcomings of the existing PVC cladding PET yarns in terms of light, thermal stability and bonding are solved, and better mechanical properties and durability are achieved.

CN119571511AInactive Publication Date: 2025-03-07常州同维佳业新材料科技有限公司
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510070444.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-03-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing PVC coated PET yarns have shortcomings in light, thermal stability and chemical corrosion resistance, and the combination of PVC and PET core wire is insufficient, resulting in poor mechanical properties and durability.

Method used

A modified PVC coating is used, and components such as zinc laurate heat stabilizer, titanium dioxide, pentaerythritol polyglycidyl ether are added to improve thermal stability and light stability; an intermediate layer is formed between the core wire and the coating layer, and materials such as polycarbonate polyurethane resin and ethylene-acrylate copolymer are used to enhance the bonding strength.

Benefits of technology

The light resistance, heat resistance and mechanical properties of PVC coated yarn are significantly improved, and the bond fastness and durability of the core wire and the cladding layer are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005245550830000121
    Figure BDA0005245550830000121
  • Figure BDA0005245550830000131
    Figure BDA0005245550830000131
  • Figure BDA0005245550830000132
    Figure BDA0005245550830000132
Patent Text Reader

Abstract

The invention discloses a PVC (polyvinyl chloride) coated yarn and a preparation process thereof, the PVC coated yarn comprises a core yarn, a modified PVC coating layer and a middle layer, the core yarn is coated with the modified PVC coating layer, the middle layer is arranged between the core yarn and the modified PVC coating layer, and the middle layer at least comprises polycarbonate type polyurethane resin and ethylene-acrylate copolymer; the preparation method comprises the following steps: S1, extruding and granulating the raw material components of the modified PVC coating layer to prepare a modified PVC master batch; s2, gluing the core wire, heating and then cooling to form a middle layer; s3, the modified PVC master batch is put into a PVC coating machine, the core yarn penetrates through a die head of the PVC coating machine, the modified PVC master batch is subjected to hot melting and extrusion, the outer surface of the core yarn is coated with the modified PVC master batch, and the PVC coated yarn is prepared. The PVC coated yarn has the advantages that the combination degree of the PVC coating layer and the core yarn is better, and the prepared PVC coated yarn is more excellent in mechanical property, better in light resistance and heat resistance and better in aging resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of textile materials, and in particular to a PVC coated yarn and a preparation process thereof. Background Art

[0002] Core-spun yarn, also known as composite yarn or covered yarn, is a new type of yarn made of two or more materials. Core-spun yarn generally uses synthetic fiber filaments with good strength and elasticity as the core yarn, and the outer side is covered with other fibers through blending, or covered with other material layers through hot melt coating process.

[0003] The coated yarn made of PVC coated PET filament is a new type of coated yarn that has emerged in recent years. PET has good heat resistance, creep resistance, fatigue resistance, friction and wear resistance, electrical insulation and chemical corrosion resistance. After being made into filaments, it has high strength, good elasticity, good weather resistance and good heat resistance. It is a high-quality synthetic fiber, but it has strong water absorption. PVC has high strength, good weather resistance, good insulation and flame retardant properties. It is a high-quality wire and cable coating material. The two materials are made into coated yarn, which can combine the advantages of both materials, so that the yarn has excellent mechanical properties, and at the same time has flame retardancy, insulation and water resistance. This new type of yarn can be used as the main material and is widely used in various tablecloths, curtains, outdoor sunshade nets or meshes, carpets or mats, interior decoration, and automotive interiors.

[0004] However, existing PVC coated PET yarns also have many problems. First, PVC has poor stability to light and heat, and is not resistant to chemical corrosion. It is easily oxidized and decomposed by long-term ultraviolet radiation. Second, PVC coated PET fibers are not easy to process. The melting temperatures of the two fibers are quite different, and the compatibility is insufficient. Whether the melt coating process or the immersion coating process is used, there are problems of insufficient bonding strength and poor durability. Summary of the invention

[0005] In order to solve at least one of the above technical problems, a PVC coated yarn with better bonding between the PVC coating and the core wire, excellent mechanical properties, and better light resistance and heat resistance is developed. The present application provides a PVC coated yarn and a preparation process thereof.

[0006] On the one hand, the present application provides a PVC coated yarn, comprising a core wire and a modified PVC coating layer coated on the outside of the core wire and an intermediate layer between the core wire and the modified PVC coating layer, wherein the intermediate layer comprises at least a polycarbonate polyurethane resin and an ethylene-acrylate copolymer; The weight proportion of each raw material component of the modified PVC coating layer is: 40-62 parts of PVC raw material, 18-22 parts of plasticizer, 0.8-1.5 parts of zinc laurate heat stabilizer, 3-4 parts of chlorinated paraffin flame retardant, 3-6 parts of titanium dioxide, 3-5 parts of calcium hydroxide powder, 5-8 parts of calcium carbonate powder, 3-4 parts of pentaerythritol polyglycidyl ether, and 2-10 parts of CPE powder.

[0007] By adopting the above technical scheme, a modified PVC coating layer is adopted in the present application, and in particular, a zinc laurate heat stabilizer is added to the PVC coating layer. This component can have a synergistic effect with calcium hydroxide micropowder, and effectively improve the thermal stability of the PVC coating layer. In addition, titanium dioxide is added to the PVC coating layer in the present application, which can effectively improve the shading effect of the coated yarn, and at the same time improve the light stability of the PVC coating layer; the addition of pentaerythritol polyglycidyl ether significantly improves the compatibility between PVC and PET core wire, improves the bonding strength, and can also improve the heat resistance and weather resistance of PVC, while the addition of titanium dioxide, calcium hydroxide micropowder and calcium carbonate micropowder can improve the hardness and wear resistance of the PVC coating layer, and the addition of CPE powder not only improves its weather resistance, but also reduces the interfacial tension between PVC and PET core wire, making it easier for PVC to be evenly coated on the PET yarn, which helps to form a tighter and firmer coating layer in the process of PVC coating PET yarn.

[0008] In addition, chlorinated paraffin flame retardant and calcium hydroxide powder are added in the present application, which not only effectively improves the flame retardant performance of the coating layer, but also significantly enhances the compatibility of PVC with other materials. In addition, calcium hydroxide powder can effectively inhibit the generation of smoke. More importantly, in the present application, an intermediate buffer connecting intermediate layer is formed between the coating layer and the core wire, and a polycarbonate polyurethane resin is added to the intermediate layer. On the one hand, it may be because the polycarbonate polyurethane resin has good mechanical strength and flex resistance, and is suitable for being used as a base material of the intermediate intermediate layer, providing a buffering effect for the high modulus industrial fiber tow and the modified PVC layer after lamination. On the other hand, it may be because the polycarbonate polyurethane is a copolymer of polycarbonate and polyurethane, and polycarbonate has a certain compatibility with PET, and polyurethane has a certain compatibility with PVC. By adjusting the polarity of the above copolymer, the compatibility between PET and PVC can be adjusted. When the polycarbonate polyurethane resin is added, the bonding performance of the core wire and the coating layer is improved, and its mechanical properties are improved.

[0009] In addition, ethylene-acrylate copolymers are added to the middle layer, and the acrylate groups in the copolymers can improve the bonding performance of the two with the ester polar groups in the PET core wire due to hydrogen bonding and dipole interaction, and the vinyl groups can be entangled with the vinyl chloride groups in the PVC coating layer to improve the compatibility and bonding strength of the two, so that the ethylene-acrylate copolymers can act as a bridge between the PET core wire and the PVC coating layer to form an overall structure and improve the bonding strength of the two; finally, the PVC coated yarn prepared in the present application not only has better heat resistance and light resistance stability, but also has excellent bonding strength, thereby having better mechanical properties and aging resistance.

[0010] Optionally, the chlorine content of the CPE powder is 32-36%.

[0011] By adopting the above technical solution, the present application ensures that CPE and PVC have excellent compatibility and bonding strength by controlling the chlorine content in the CPE powder, thereby helping to form a tighter and stronger coating layer during the PVC coating of the PET yarn.

[0012] Optionally, the core wire is made of high modulus industrial fiber bundle.

[0013] Optionally, the high modulus industrial fiber tow is selected from one of polyester industrial fiber tow, glass fiber tow or aramid fiber tow.

[0014] Optionally, the particle size of the titanium dioxide is 100 to 500 nm.

[0015] Optionally, the middle layer comprises the following raw materials in parts by weight: 10 to 35 parts of polycarbonate polyurethane resin, 22 to 30 parts of ethylene-acrylate copolymer, 20 to 25 parts of CPE powder, 6 to 10 parts of butyl carbitol acetate, 3 to 5 parts of pyromellitic anhydride and 6 to 9 parts of hydrophobically modified montmorillonite.

[0016] Optionally, the ethylene-acrylic acid ester copolymer is ethylene-ethyl acrylate copolymer EEA or ethylene-methyl acrylate copolymer EMA.

[0017] By adopting the above technical scheme, the CPE powder in the middle layer of the present application can be fused with the CPE powder and PVC in the PVC coating layer under heating conditions. On the one hand, butyl carbitol acetate acts as a plasticizer to reduce the glass transition temperature of the PVC coating layer, making it easier to form a tight bond with the PET core wire during processing. On the other hand, it can also improve the flexibility of PVC, so that the coating layer can better fit the PET core wire under the action of external force. It can also wet the surface of the PET core wire to form a thin film that forms good adhesion with the PVC coating layer, thereby improving the bonding strength between the PET core wire and the PVC coating layer.

[0018] The addition of pyromellitic dianhydride as a multifunctional acid anhydride structure contains anhydride groups that can form ester bonds with pentaerythritol polyglycidyl ether to improve the bonding strength with the PET core wire, and the introduction of its benzene ring group has an effect on polarity and heat resistance, ultimately improving the aging resistance and mechanical properties of the coated yarn, and the addition of hydrophobic modified montmorillonite can be compatible with PVC non-polar materials, and the hydrophobic modified montmorillonite can be used as an intermediate layer filler to reduce the interfacial tension between PVC and PET on the one hand, and more importantly, it can fill the gap between the two to form a tight bonding layer, thereby improving the bonding strength between the PVC coating and the PET. Finally, the addition of the intermediate buffer bonding layer in the present application significantly improves the bonding strength between the PVC coating and the core wire, and improves its durability.

[0019] Optionally, the core wire is coated after being activated by ammonia plasma, the ammonia plasma treatment pressure is controlled to be 180-220 Pa, the ammonia flow rate is 100-150 sccm, the plasma treatment power is 150-300 W, and the treatment time is 12-20 min.

[0020] By adopting the above technical scheme, the core wire is treated with ammonia plasma in the present application, and amino groups are grafted on the surface of the core wire. As an active group, the amino group introduced on the surface of the core wire can form hydrogen bonds and van der Waals forces with the hydroxyl groups in the pentaerythritol polyglycidyl ether in the PVC coating layer, and can form chemical reactions with the epoxy functional groups. Moreover, the introduced amino functional groups can also form chemical bonds with butyl carbitol acetate and pyromellitic dianhydride in the intermediate layer, thereby further improving the bonding strength and durability of the final coated yarn. It is found that the bonding strength between the core wire and the coating layer can be significantly improved after the core wire is treated with ammonia plasma, thereby improving the mechanical properties of the coated yarn.

[0021] Optionally, the hydrophobically modified montmorillonite is prepared by the following method: Sa, mixing montmorillonite with ethyl acetate, then heating to 65-75°C, then adding initiator, adding tert-butyl ester and acrylic acid, keeping the temperature for reaction for 1-2 hours, filtering, washing, and drying to obtain primary modified montmorillonite; Sb, prepare an ethanol solution with a concentration of 75%, and then add KH550 coupling agent into the ethanol solution to prepare a coupling agent solution; Sc, placing the primary modified montmorillonite obtained in step Sa into the coupling agent solution of step Sb, fully mixing, and then ultrasonically dispersing for 30 minutes to obtain a dispersed reaction solution; Sd. The dispersed reaction liquid of step Sc is reacted under closed conditions at a temperature of 75-80° C., the solid product is filtered out, and then placed in an oven and dried with hot air to constant weight to obtain a hydrophobically modified montmorillonite.

[0022] By adopting the above technical scheme, in the present application, montmorillonite is firstly placed in a solvent, and tert-butyl vinyl carbonate and acrylic acid are grafted under the action of an initiator to form a tert-butyl carbonate group at one end and a carboxylic acid group at the other end. The carboxylic acid end group in the copolymer is chemically bonded to the hydroxyl group on the surface of the montmorillonite under high temperature conditions to achieve the introduction of the graft copolymer on the surface of the montmorillonite. The end group is a tert-butyl carbonate group, which significantly improves the hydrophobicity of the montmorillonite and forms a great steric hindrance to solve its agglomeration problem, which helps to evenly distribute the montmorillonite in the glue, and then can play a better role in filling the pores between the core wire and the coating layer and improving the bonding strength between the two. On the other hand, a part of the carboxyl groups in the graft copolymer in the present application can also form chemical bonds with the amino groups on the core wire after ammoniation modification, further improving the bonding strength between the coating and the core material, and ultimately improving the coating firmness; and then it is modified in a silane coupling agent to further improve its hydrophobicity and improve its compatibility and dispersibility in the organic glue system.

[0023] Optionally, during the preparation of the hydrophobically modified montmorillonite, the initiator is dibenzoyl peroxide or azobisisobutyronitrile.

[0024] Optionally, during the preparation of the hydrophobically modified montmorillonite, the mass ratio of montmorillonite to ethyl acetate is 1:(3-4), the amount of the initiator added is 0.5-1.5wt% of the montmorillonite, and the mass ratio of montmorillonite, versatate and acrylic acid added is 1:(0.4-0.6):(0.3-0.5); The mass ratio of KH550 coupling agent to ethanol solution is 1:(2-4), and the mass ratio of primary modified montmorillonite to coupling agent solution is 1:(4-5).

[0025] On the other hand, the present application also provides a method for preparing the above-mentioned PVC coated yarn, comprising the following steps: S1. Extruding and granulating the raw material components of the modified PVC coating layer according to the formula amount through an extruder to obtain a modified PVC masterbatch; S2, coating the core wire with glue, heating it to 120-160°C and then cooling it to room temperature to form an intermediate layer on the outer surface of the core wire; S3, putting the modified PVC masterbatch obtained in step S1 into a PVC coating machine, passing the core wire treated in step S2 into the die head of the PVC coating machine, and using the PVC coating machine to hot-melt and extrude the modified PVC masterbatch, and coating it on the outer surface of the core wire to obtain PVC coated yarn.

[0026] By adopting the above technical scheme, the present application prepares PVC masterbatch through an extrusion process, and then uses a PVC coating machine to coat the outer surface of the core wire with a PVC coating layer by hot melting and extrusion. The entire process is relatively simple and easy to process in batches. In addition, the coating process of the present application first adopts a coating method to form an intermediate layer on the outer surface of the high modulus industrial fiber tow, and then the modified PVC is coated. The obtained coated yarn coating layer has a better bonding with the core wire.

[0027] Optionally, in step S1, the preparation of the modified PVC masterbatch comprises the following steps: S1-1, fully mixing the formulated amount of PVC raw materials, CPE powder, chlorinated paraffin flame retardant and zinc laurate heat stabilizer, and preparing a PVC mixture by mixing and granulating; S1-2, mixing the titanium dioxide, calcium hydroxide powder, calcium carbonate powder and pentaerythritol polyglycidyl ether in the formula amount, heating to 80-90° C. with constant temperature stirring, and cooling to obtain a mixed auxiliary material; S1-3, the PVC mixed material obtained in step S1-1 and the mixed auxiliary material obtained in step S1-2 are extruded and granulated by a twin-screw extruder to obtain a modified PVC masterbatch.

[0028] By adopting the above technical scheme, in step S1-2, pentaerythritol polyglycidyl ether is blended with titanium dioxide, calcium hydroxide micropowder, and calcium carbonate micropowder under heating conditions, and active groups such as hydroxyl groups on the surface of the inorganic filler react with epoxy groups or hydroxyl groups in pentaerythritol polyglycidyl ether to form a bond, so that the inorganic filler is evenly dispersed in the pentaerythritol polyglycidyl ether liquid, so that after the mixed auxiliary materials are mixed with the PVC mixed material, the inorganic filler can be evenly dispersed in the modified PVC masterbatch, so that the performance of the coated yarn is further improved.

[0029] Optionally, the screw speed of the twin-screw extruder is 320-330 rpm, and the temperature of each section is: zone one 155-160°C, zone two 160-165°C, zone three 165-170°C, zone four 170-175°C, zone five 160-165°C.

[0030] Optionally, in step S3, during coating, the extrusion temperature of the modified PVC masterbatch is controlled at 164-168° C., and the die head temperature of the PVC coating machine is controlled at 172-176° C.

[0031] In summary, the present invention includes at least one of the following beneficial technical effects: 1. The present application adds zinc laurate heat stabilizer to the PVC coating layer. This component can have a synergistic effect with calcium hydroxide micropowder to effectively improve the thermal stability of the PVC coating layer. In addition, the present application adds titanium dioxide to the PVC coating layer, which can effectively improve the shading effect of the coated yarn and improve the light stability of the PVC coating layer.

[0032] 2. The present application prepares PVC masterbatch by extrusion, and then uses a PVC coating machine to coat the outer surface of the core wire with a PVC coating layer by hot melt and extrusion. The entire process is relatively simple and easy to process in batches. At the same time, the present application also uses a glue coating process and selects a specific glue formula to form an intermediate layer on the surface of the high modulus industrial fiber bundle, so that the formed core wire and the PVC coating layer are better bonded. DETAILED DESCRIPTION

[0033] The present application is further described in detail below with reference to the embodiments.

[0034] The current PVC coated PET yarn has the problem of poor light and heat stability of the coating layer and poor resistance to chemical corrosion; the insufficient bonding between PVC and PET core wire leads to insufficient mechanical properties of the coated yarn; the coated yarn uses chlorine-containing materials, which will produce a large amount of toxic smoke when exposed to fire; the PVC coating of the coated yarn uses toxic plasticizers, compatibilizers and other additives, as well as toxic flame retardant and smoke suppression components. In response to the above problems, this application designs a modification system for the PVC coating layer and also makes corresponding improvements to the process of the bonding part between the PVC coating layer and the core wire.

[0035] For the PVC coating, the present application designs a specific blending modification system, which combines stability modification, chemical corrosion resistance modification, compatibility modification and flame retardant modification. The PVC coating of the present application adopts a modification system of PVC, CPE, zinc laurate heat stabilizer and calcium hydroxide. After PVC and CPE are blended, and a calcium / zinc composite stabilizer of zinc laurate and calcium hydroxide is added, the softness, chemical corrosion resistance, and thermal stability of PVC can be effectively improved; and the present application also designs a filler system of titanium dioxide and calcium carbonate, which can not only enhance the mechanical properties of the PVC coating, but also effectively improve the light-shielding and light stability of the PVC coating. The present application adds a chlorinated paraffin flame retardant to the above-mentioned modification system. The introduction of this component can be used as a solubilizer or lubricant to improve the compatibility between PVC and other components, and at the same time improve the flame retardant performance. The calcium hydroxide component in the calcium / zinc composite stabilizer can also play a smoke suppression effect after encountering a fire, and can absorb chlorine-containing toxic gases.

[0036] For the bonding part between the PVC coating layer and the core wire, the present application uses a high modulus industrial fiber bundle to be coated with a special glue to form an intermediate layer to prepare the core wire. The intermediate layer prepared by using polycarbonate polyurethane resin, ethylene-acrylate copolymer, CPE powder, butyl carbitol acetate, pyromellitic anhydride, and hydrophobically modified montmorillonite and the PVC coating layer and the high modulus industrial fiber bundle all have better bonding strength through corresponding reactions, so that the prepared PVC coated yarn has better bonding strength and durability.

[0037] The invention is described below in conjunction with specific embodiments.

[0038] The main raw materials of the following examples are as follows: PVC raw materials were purchased from Formosa Plastics (Ningbo) Co., Ltd.; CPE powder, with a chlorine content of about 34%, was purchased from Linyi Anfeng Chemical Co., Ltd.; zinc laurate thermal stabilizer was purchased from Yantai Zhaoyi Biotechnology Co., Ltd.; chlorinated paraffin, CE-70, was purchased from Wuhan Jiyesheng Chemical Co., Ltd.; titanium dioxide, with a particle size of 300 nanometers, was purchased from DuPont, USA; calcium hydroxide micropowder, 325 mesh, was purchased from Shenyang Ketuo Chemical Co., Ltd.; calcium carbonate micropowder was a micropowder with a fineness of 400 mesh; The plasticizer in the embodiments of the present application is dioctyl terephthalate purchased from Shandong Lanfan Chemical Group; the polycarbonate polyurethane resin is a polycarbonate polyurethane dispersion of model Bayhydrol U 2757 produced by Covestro, and the ethylene-acrylate copolymer is ethylene-ethyl acrylate copolymer EEA is EEA2615AC produced by DuPont of the United States.

[0039] The following preparation example is a preparation example of hydrophobically modified montmorillonite: Preparation Example 1 A method for preparing hydrophobically modified montmorillonite comprises the following steps: Sa, montmorillonite and ethyl acetate are mixed in a mass ratio of 1:3.5, and then the temperature is raised to 70°C, and then dibenzoyl peroxide as an initiator is added, tert-butyl ester and acrylic acid are added, and the mixture is kept warm for 1.5 hours, filtered, washed, and dried to obtain primary modified montmorillonite, the amount of the initiator added is 1wt% of the montmorillonite, and the mass ratio of montmorillonite, tert-butyl ester and acrylic acid added is 1:(0.5):0.4; Sb, prepare an ethanol solution with a concentration of 75%, and then add KH550 coupling agent to the ethanol solution to prepare a coupling agent solution, and the added mass ratio of KH550 coupling agent to ethanol solution is 1:3; Sc, placing the primary modified montmorillonite obtained in step Sa in the coupling agent solution of step Sb, fully mixing, and then ultrasonically dispersing for 30 minutes to obtain a dispersed reaction solution, wherein the added mass ratio of the primary modified montmorillonite to the coupling agent solution is 1:4.5; Sd. The dispersed reaction liquid of step Sc is reacted for 45 minutes at 75° C. under closed conditions, the solid product is filtered out, and then placed in an oven at 75° C. and dried with hot air to constant weight to obtain hydrophobically modified montmorillonite.

[0040] Preparation Example 2 A method for preparing hydrophobically modified montmorillonite comprises the following steps: Sa, montmorillonite and ethyl acetate are mixed in a mass ratio of 1:3, and then the temperature is raised to 65°C, and then dibenzoyl peroxide as an initiator is added, tert-butyl ester and acrylic acid are added, and the mixture is kept warm for 2 hours, filtered, washed, and dried to obtain primary modified montmorillonite, the amount of the initiator added is 0.5wt% of the montmorillonite, and the mass ratio of montmorillonite, tert-butyl ester and acrylic acid added is 1:0.4:0.3; Sb, prepare an ethanol solution with a concentration of 75%, and then add KH550 coupling agent to the ethanol solution to prepare a coupling agent solution, and the added mass ratio of KH550 coupling agent to ethanol solution is 1:2; Sc, placing the primary modified montmorillonite obtained in step Sa in the coupling agent solution of step Sb, fully mixing, and then ultrasonically dispersing for 30 minutes to obtain a dispersed reaction liquid, wherein the added mass ratio of the primary modified montmorillonite to the coupling agent solution is 1:4; Sd. The dispersed reaction liquid of step Sc is reacted for 45 minutes at 75° C. under closed conditions, the solid product is filtered out, and then placed in an oven at 75° C. and dried with hot air to constant weight to obtain hydrophobically modified montmorillonite.

[0041] Preparation Example 3 A method for preparing hydrophobically modified montmorillonite comprises the following steps: Sa, montmorillonite and ethyl acetate are mixed in a mass ratio of 1:4, and then the temperature is raised to 75°C, and then dibenzoyl peroxide as an initiator is added, tert-butyl ester and acrylic acid are added, and the mixture is kept warm for 1 hour, filtered, washed, and dried to obtain primary modified montmorillonite, the amount of the initiator added is 1.5wt% of the montmorillonite, and the mass ratio of montmorillonite, tert-butyl ester and acrylic acid added is 1:0.6:0.5; Sb, prepare an ethanol solution with a concentration of 75%, and then add KH550 coupling agent to the ethanol solution to prepare a coupling agent solution, and the added mass ratio of KH550 coupling agent to ethanol solution is 1:4; Sc, placing the primary modified montmorillonite obtained in step Sa in the coupling agent solution of step Sb, fully mixing, and then ultrasonically dispersing for 30 minutes to obtain a dispersed reaction solution, wherein the added mass ratio of the primary modified montmorillonite to the coupling agent solution is 1:5; Sd. The dispersed reaction liquid of step Sc is reacted for 45 minutes at 80° C. under closed conditions, the solid product is filtered out, and then placed in an oven at 75° C. and dried with hot air to constant weight to obtain hydrophobically modified montmorillonite.

[0042] Preparation Example 4 A method for preparing hydrophobically modified montmorillonite is carried out according to the method in Preparation Example 1, except that step Sa is not carried out, and the primary modified montmorillonite in step Sc is replaced by montmorillonite in an equal amount.

[0043] Example 1 The PVC coated yarn of this embodiment is prepared by the following steps: S1. According to the formula, the raw material components of the modified PVC coating layer are extruded and granulated through an extruder to obtain a modified PVC masterbatch. The specific operation is as follows: S1-1, 50kg PVC raw material, 20kg plasticizer, 5kg CPE powder, 3.5kg chlorinated paraffin flame retardant, 1.2kg zinc laurate heat stabilizer, 0.1kg antioxidant, 0.5kg light stabilizer and 0.2kg lubricant were fully mixed, and granulated to obtain a PVC mixture, wherein the antioxidant was antioxidant 1076 purchased from BASF, Germany; the light stabilizer was 2-hydroxy-4-n-octyloxybenzophenone purchased from BASF, Germany; the lubricant was polyethylene wax purchased from Clariant; S1-2, 5 kg titanium dioxide, 4 kg calcium hydroxide powder, 6 kg calcium carbonate powder and 3 kg pentaerythritol polyglycidyl ether were mixed, heated to 85° C. with constant temperature stirring, and cooled to obtain a mixed auxiliary material; S1-3. The PVC mixture obtained in step S1-1 and the mixed auxiliary materials obtained in step S1-2 are extruded and granulated through a twin-screw extruder to obtain a modified PVC masterbatch. The screw speed of the twin-screw extruder is 320 rpm, and the temperatures of each section are: 155° C. in zone 1, 160° C. in zone 2, 165° C. in zone 3, 170° C. in zone 4, and 160° C. in zone 5.

[0044] S2. A polyester industrial fiber tow with a linear density of 500D, a breaking strength of about 8.4g / D, a breaking elongation of 20%, and a dry heat shrinkage of 2.5% (177°C, 1min 0.01g / D) is selected as a high modulus industrial fiber tow as a core wire, and the polyester industrial fiber tow is laid out through a glue coating tank. A scraping hole adapted to the diameter of the tow is provided at a portion of the glue coating tank for the tow to pass through, so as to make the glue layer of the tow have better coating controllability after the glue coating, and a glue receiving tank for receiving the glue liquid is provided on the outer groove wall of the glue coating tank. After the glue coating treatment, the tow continuously enters a heating oven and a cooling box. The temperature in the oven is 150°C. The cooling box cools the tow to room temperature, and forms an intermediate layer on the outer surface of the polyester industrial fiber tow core wire; The coating tank contains a glue solution obtained by mixing the following raw materials, and the coating tank temperature is 40°C: 25kg polycarbonate polyurethane resin, 26kg ethylene-acrylate copolymer, 22kg CPE powder, 8kg butyl carbitol acetate, 4kg pyromellitic dianhydride, 7kg hydrophobically modified montmorillonite prepared in Preparation Example 1, and 12kg solvent, wherein the solvent is acetone and water in a mass ratio of 8:2; S3. Put the modified PVC masterbatch obtained in step S1 into a PVC coating machine, insert the core wire treated in step S2 into the die head of the PVC coating machine, and use the PVC coating machine to hot-melt and extrude the modified PVC masterbatch, and coat it on the outer surface of the core wire to obtain PVC coated yarn, wherein the extrusion temperature of the modified PVC masterbatch is controlled at 165° C., and the die head temperature of the PVC coating machine is controlled at 174° C.

[0045] Example 2 The difference between this embodiment and embodiment 1 lies in the ratio of the modified PVC masterbatch.

[0046] The PVC coated yarn of this embodiment is prepared by the following steps: S1. According to the formula, the raw material components of the modified PVC coating layer are extruded and granulated through an extruder to obtain a modified PVC masterbatch. The specific operation is as follows: S1-1, 40kg PVC raw material, 18kg plasticizer, 2kg CPE powder, 3kg chlorinated paraffin flame retardant, 0.8kg zinc laurate heat stabilizer, 0.1kg antioxidant, 0.5kg light stabilizer and 0.2kg lubricant were fully mixed, and granulated to obtain a PVC mixture, wherein the antioxidant was antioxidant 1076 purchased from BASF, Germany; the light stabilizer was 2-hydroxy-4-n-octyloxybenzophenone purchased from BASF, Germany; the lubricant was polyethylene wax purchased from Clariant; S1-2, mix 3kg of titanium dioxide, 3kg of calcium hydroxide powder, 5kg of calcium carbonate powder and 3kg of pentaerythritol polyglycidyl ether, heat to 80°C with constant temperature stirring, and cool to obtain a mixed auxiliary material; S1-3. The PVC mixture obtained in step S1-1 and the mixed auxiliary materials obtained in step S1-2 are extruded and granulated through a twin-screw extruder to obtain a modified PVC masterbatch. The screw speed of the twin-screw extruder is 320 rpm, and the temperatures of each section are: 155° C. in zone 1, 160° C. in zone 2, 165° C. in zone 3, 170° C. in zone 4, and 160° C. in zone 5.

[0047] S2. A polyester industrial fiber tow with a linear density of 500D, a breaking strength of about 8.4g / D, a breaking elongation of 20%, and a dry heat shrinkage of 2.5% (177°C, 1min 0.01g / D) is selected as a high modulus industrial fiber tow as a core wire, and the polyester industrial fiber tow is laid out through a glue coating tank. A scraping hole adapted to the diameter of the tow is provided at a portion of the glue coating tank for the tow to pass through, so as to make the glue layer of the tow have better coating controllability after the glue coating, and a glue receiving tank for receiving the glue liquid is provided on the outer groove wall of the glue coating tank. After the glue coating treatment, the tow continuously enters a heating oven and a cooling box. The temperature in the oven is 150°C. The cooling box cools the tow to room temperature, and forms an intermediate layer on the outer surface of the polyester industrial fiber tow core wire; The coating tank contains a glue solution obtained by mixing the following raw materials, and the coating tank temperature is 35°C: 10kg polycarbonate polyurethane resin, 22kg ethylene-acrylate copolymer, 20kg CPE powder, 6kg butyl carbitol acetate, 3kg pyromellitic dianhydride and 6kg hydrophobically modified montmorillonite prepared in Preparation Example 2 and 8kg solvent, and the solvent is selected from acetone and water in a mass ratio of 8:2; S3. Put the modified PVC masterbatch obtained in step S1 into a PVC coating machine, insert the core wire treated in step S2 into the die head of the PVC coating machine, and use the PVC coating machine to hot-melt and extrude the modified PVC masterbatch, and coat it on the outer surface of the core wire to obtain PVC coated yarn, wherein the extrusion temperature of the modified PVC masterbatch is controlled at 164° C., and the die head temperature of the PVC coating machine is controlled at 172° C.

[0048] Example 3 The PVC coated yarn of this embodiment is prepared by the following steps: S1. According to the formula, the raw material components of the modified PVC coating layer are extruded and granulated through an extruder to obtain a modified PVC masterbatch. The specific operation is as follows: S1-1, 62kg PVC raw material, 22kg plasticizer, 10kg CPE powder, 4kg chlorinated paraffin flame retardant, 1.5kg zinc laurate heat stabilizer, 0.1kg antioxidant, 0.5kg light stabilizer and 0.2kg lubricant were fully mixed, and granulated to obtain a PVC mixture, wherein the antioxidant was antioxidant 1076 purchased from BASF, Germany; the light stabilizer was 2-hydroxy-4-n-octyloxybenzophenone purchased from BASF, Germany; the lubricant was polyethylene wax purchased from Clariant; S1-2, mix 6 kg titanium dioxide, 5 kg calcium hydroxide powder, 8 kg calcium carbonate powder and 4 kg pentaerythritol polyglycidyl ether, heat to 90° C. with constant temperature stirring, and cool to obtain a mixed auxiliary material; S1-3. The PVC mixture obtained in step S1-1 and the mixed auxiliary materials obtained in step S1-2 are extruded and granulated through a twin-screw extruder to obtain a modified PVC masterbatch. The screw speed of the twin-screw extruder is 330 rpm, and the temperatures of each section are: 160° C. in zone 1, 165° C. in zone 2, 170° C. in zone 3, 175° C. in zone 4, and 165° C. in zone 5.

[0049] S2. A polyester industrial fiber tow with a linear density of 500D, a breaking strength of about 8.4g / D, a breaking elongation of 20%, and a dry heat shrinkage of 2.5% (177°C, 1min 0.01g / D) is selected as a high modulus industrial fiber tow as a core wire, and the polyester industrial fiber tow is laid out through a glue coating tank. A scraping hole adapted to the diameter of the tow is provided at a portion of the glue coating tank for the tow to pass through, so as to make the glue layer of the tow have better coating controllability after the glue coating, and a glue receiving tank for receiving the glue liquid is provided on the outer groove wall of the glue coating tank. After the glue coating treatment, the tow continuously enters a heating oven and a cooling box. The temperature in the oven is 150°C. The cooling box cools the tow to room temperature, and forms an intermediate layer on the outer surface of the polyester industrial fiber tow core wire; The coating tank contains a glue solution obtained by mixing the following raw materials, and the coating tank temperature is 45°C: 35kg polycarbonate polyurethane resin, 30kg ethylene-acrylate copolymer, 25kg CPE powder, 10kg butyl carbitol acetate, 5kg pyromellitic dianhydride, 9kg hydrophobically modified montmorillonite prepared in Preparation Example 3, and 15kg solvent, wherein the solvent is acetone and water in a mass ratio of 8:2; S3. Put the modified PVC masterbatch obtained in step S1 into a PVC coating machine, insert the core wire treated in step S2 into the die head of the PVC coating machine, and use the PVC coating machine to hot-melt and extrude the modified PVC masterbatch, and coat it on the outer surface of the core wire to obtain PVC coated yarn, wherein the extrusion temperature of the modified PVC masterbatch is controlled at 168° C., and the die head temperature of the PVC coating machine is controlled at 176° C.

[0050] Example 4 The difference between this embodiment and embodiment 1 is that the hydrophobically modified montmorillonite of the glue solution in the glue coating tank in step S2 is the hydrophobically modified montmorillonite prepared in Preparation Example 4.

[0051] Example 5 The difference between this embodiment and embodiment 1 is that in step S2, no hydrophobically modified montmorillonite is added to the glue in the glue coating tank.

[0052] Example 6 The difference between this embodiment and embodiment 1 is that in step S2, the hydrophobically modified montmorillonite in the glue solution in the glue coating tank is replaced by montmorillonite in equal amounts.

[0053] Example 7 The difference between this embodiment and embodiment 1 is that no CPE powder is added to the glue in the glue coating tank in step S2.

[0054] Example 8 The difference between this embodiment and embodiment 1 is that in step S2, no pyromellitic anhydride is added to the glue in the glue coating tank.

[0055] Example 9 The difference between this embodiment and embodiment 1 is that the parameters of the coating in step S3 are set differently. Specifically, During coating in this embodiment, the extrusion temperature of the modified PVC masterbatch is 175°C, and the die head temperature of the PVC coating machine is 180°C.

[0056] Example 10 The difference between this embodiment and embodiment 1 is that the polyester industrial fiber tow in this embodiment is pretreated before being coated with glue, specifically: the polyester industrial fiber tow is placed in a plasma device for ammonia plasma activation treatment, the ammonia plasma treatment pressure is controlled to 200Pa, the ammonia flow rate is 120sccm, the plasma processing power is 200W, and the processing time is 15min.

[0057] Embodiment 11 The difference between this embodiment and embodiment 1 is that the polyester industrial fiber tow in this embodiment is pretreated before being coated with glue, specifically: the polyester industrial fiber tow is placed in a plasma device for ammonia plasma activation treatment, the ammonia plasma treatment pressure is controlled to 180Pa, the ammonia flow rate is 100sccm, the plasma processing power is 150W, and the processing time is 20min.

[0058] Example 12 The difference between this embodiment and embodiment 1 is that the polyester industrial fiber tow in this embodiment is pretreated before being coated with glue, specifically: the polyester industrial fiber tow is placed in a plasma device for ammonia plasma activation treatment, the ammonia plasma treatment pressure is controlled to 220Pa, the ammonia flow rate is 150sccm, the plasma processing power is 300W, and the processing time is 12min.

[0059] Comparative Example 1 The difference between this comparative example and Example 1 is that step S2 is not performed, the polyester industrial fiber tow is not subjected to the glue coating treatment, and the high modulus industrial fiber tow is directly coated with the modified PVC masterbatch.

[0060] Comparative Example 2 The difference between this comparative example and Example 1 is that no polycarbonate polyurethane resin is added to the raw materials of the intermediate layer formed by the glue coating in step S2.

[0061] Comparative Example 3 The difference between this comparative example and Example 1 is that no ethylene-acrylate copolymer is added to the raw materials of the intermediate layer formed by the glue coating in step S2.

[0062] Comparative Example 4 The difference between this comparative example and Example 1 is that pentaerythritol polyglycidyl ether is not added to the modified PVC masterbatch raw material.

[0063] Comparative Example 5 The difference between this comparative example and Example 1 is that in the ratio of the modified PVC masterbatch, an equal amount of calcium carbonate powder is used to replace calcium hydroxide powder.

[0064] Comparative Example 6 The difference between this comparative example and Example 1 is that no CPE powder is added in the ratio of the modified PVC masterbatch.

[0065] Comparative Example 7 The difference between this comparative example and Example 1 is that in the preparation process of the coated yarn, the modified PVC masterbatch is not prepared, and the raw materials of the modified PVC coating layer are directly mixed and added to the PVC coating machine as a mixed raw material.

[0066] Performance Testing In order to more intuitively detect the bonding strength between the coating layer and the core wire in the coated yarn prepared in the present application, the peel strength (N·mm) of the coated yarn in the present embodiment and the comparative example was measured with reference to FZ / T 01010-2012 "Determination of peel strength of coating on coated fabrics" -1 The test results of ) (peel force per unit width) are shown in Table 1 below.

[0067] Table 1 In addition, the mechanical properties of the coated yarns prepared in the examples and comparative examples of the present application were tested using the method described in GB / T14344-2008; the coated yarns were then placed in a UV oven at a humidity of 150% and a temperature of 65°C, aged for 30 days under UV irradiation, and the mechanical properties were tested again. The test results obtained from this test experiment are shown in Table 1.

[0068] Table 2 Mechanical properties test table of examples and comparative examples It can be seen from the data in Table 1 and Table 2 that the coating layer and the core wire in the embodiment of the present application have good bonding strength, and the obtained coated yarn has good mechanical properties. Combined with the test results in Example 1, Example 4 and Example 5, it can be seen that when the montmorillonite is hydrophobically modified only by using a silane coupling agent for hydrophobic modification, the bonding force between the coating layer and the core wire is improved compared with Example 5, and the mechanical properties are improved, but it is still far weaker than Example 1, especially the mechanical properties are reduced in the later stage of the aging test. Combined with the test results of Example 6, when the montmorillonite in Example 6 is not hydrophobically modified, it will affect its distribution in the coating, thereby affecting the bonding strength between the coating layer and the core wire, and further affecting the mechanical properties of the coated yarn.

[0069] Referring to the test results of Example 1 and Example 7, when CPE was not added to the glue in Example 7, its mechanical properties were also significantly reduced, especially the aging performance. This is because the addition of CPE can not only improve the processing performance of PVC and help improve the coating quality, but also CPE has good compatibility with PVC. The addition of CPE in the middle layer helps to improve the compatibility between PVC and the core wire and play a buffering role, thereby improving the bonding firmness and mechanical properties. Combined with the test results of Example 8, when pyromellitic anhydride was not added to the glue, it would affect the chemical bonding such as cross-linking between the middle layer and the core wire and the coating layer, resulting in a reduction in the bonding between the core wire and the coating layer, thereby reducing its mechanical properties and aging performance. Combined with the test results of Example 1 and Example 9, the coating process parameters affect the coating quality, and then affect the mechanical properties of the coated yarn. Combined with the test results of Examples 10-12, the core wire is activated by ammonia plasma and then coated with glue, which helps to introduce ammonium ions into the core wire, and then the chemical connection between the intermediate layer and the coating layer can be strengthened, thereby significantly improving its bonding strength, mechanical properties and anti-aging properties.

[0070] Referring to the test results of Example 1 and Comparative Example 1, there is no intermediate buffer transition connection layer formed between the core wire and the coating layer. The PVC coating layer is directly coated on the core wire, and its bonding strength is significantly reduced, and the mechanical properties and anti-aging properties are significantly reduced. This is because the compatibility between PVC and polyester PET core wire is poor, and the reduced bonding strength affects its performance. Combined with the test results of Comparative Examples 2 and 3, when only one of polycarbonate polyurethane resin or ethylene-acrylate copolymer is added to the resin raw material in the intermediate layer, its mechanical properties are reduced, which will affect the coating layer and the core wire. Referring to Comparative Example 4, when no pentaerythritol polyglycidyl ether was added to the modified PVC masterbatch, its mechanical properties were significantly reduced. Referring to Comparative Example 5, when calcium carbonate replaced calcium hydroxide, its mechanical properties and anti-aging properties were reduced. The zinc laurate heat stabilizer and calcium hydroxide synergistically improved the thermal stability of the PVC coated yarn. When no CPE powder was added in Comparative Example 6, its performance was also reduced. Referring to the test results of Comparative Example 7, when preparing the PVC coating layer, if the raw materials are not made into a masterbatch in advance, the mechanical properties of the coated yarn will be significantly affected.

[0071] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. A PVC coated yarn, characterized in that: It comprises a core wire, a modified PVC coating layer coated on the outside of the core wire, and an intermediate layer between the core wire and the modified PVC coating layer, wherein the intermediate layer comprises at least a polycarbonate polyurethane resin and an ethylene-acrylate copolymer; The weight proportion of each raw material component of the modified PVC coating layer is: 40-62 parts of PVC raw material, 18-22 parts of plasticizer, 0.8-1.5 parts of zinc laurate heat stabilizer, 3-4 parts of chlorinated paraffin flame retardant, 3-6 parts of titanium dioxide, 3-5 parts of calcium hydroxide powder, 5-8 parts of calcium carbonate powder, 3-4 parts of pentaerythritol polyglycidyl ether, and 2-10 parts of CPE powder.

2. The PVC coated yarn according to claim 1, characterized in that: The chlorine content of the CPE powder is 32-36%.

3. The PVC coated yarn according to claim 1, characterized in that: The core wire is made of high modulus industrial fiber bundle.

4. The PVC coated yarn according to claim 3, characterized in that: The high modulus industrial fiber tow is selected from one of polyester industrial fiber tow, glass fiber tow or aramid fiber tow.

5. The PVC coated yarn according to claim 1, characterized in that: The intermediate layer comprises the following raw materials in parts by weight: 10-35 parts of polycarbonate polyurethane resin, 22-30 parts of ethylene-acrylate copolymer, 20-25 parts of CPE powder, 6-10 parts of butyl carbitol acetate, 3-5 parts of pyromellitic dianhydride and 6-9 parts of hydrophobically modified montmorillonite.

6. The PVC coated yarn according to claim 1, characterized in that: The core wire is coated after being activated by ammonia plasma. The ammonia plasma treatment pressure is controlled to be 180-220 Pa, the ammonia flow rate is 100-150 sccm, the plasma treatment power is 150-300 W, and the treatment time is 12-20 min.

7. A method for preparing the PVC coated yarn according to claim 1, characterized in that: The following steps are involved: S1. Extruding and granulating the raw material components of the modified PVC coating layer according to the formula amount through an extruder to obtain a modified PVC masterbatch; S2, coating the core wire with glue, heating it to 120-160°C and then cooling it to room temperature to form an intermediate layer on the outer surface of the core wire; S3, putting the modified PVC masterbatch obtained in step S1 into a PVC coating machine, passing the core wire treated in step S2 into the die head of the PVC coating machine, and using the PVC coating machine to hot-melt and extrude the modified PVC masterbatch, and coating it on the outer surface of the core wire to obtain PVC coated yarn.

8. The method for preparing PVC coated yarn according to claim 7, characterized in that: In step S1, the preparation of the modified PVC masterbatch comprises the following steps: S1-1, fully mixing the formulated amount of PVC raw materials, CPE powder, chlorinated paraffin flame retardant and zinc laurate heat stabilizer, and preparing a PVC mixture by mixing and granulating; S1-2, mixing the titanium dioxide, calcium hydroxide powder, calcium carbonate powder and pentaerythritol polyglycidyl ether in the formula amount, heating to 80-90° C. with constant temperature stirring, and cooling to obtain a mixed auxiliary material; S1-3, the PVC mixed material obtained in step S1-1 and the mixed auxiliary material obtained in step S1-2 are extruded and granulated by a twin-screw extruder to obtain a modified PVC masterbatch.

9. The method for preparing PVC coated yarn according to claim 8, characterized in that: The screw speed of the twin-screw extruder is 320-330 rpm, and the temperature of each section is: zone 1 155-160°C, zone 2 160-165°C, zone 3 165-170°C, zone 4 170-175°C, zone 5 160-165°C.

10. The method for preparing PVC coated yarn according to claim 7, characterized in that: In the step S3, during coating, the extrusion temperature of the modified PVC masterbatch is controlled at 164-168° C., and the die head temperature of the PVC coating machine is controlled at 172-176° C.

Citation Information

Patent Citations

  • PVC (polyvinyl chloride) thermoplastic elastomer yarn and preparation method thereof

    CN109763225A

  • Flaky calcium-zinc PVC heat stabilizer and preparation method thereof

    CN112852067A

  • Black-out cloth fabric and manufacturing method

    CN118029036A

  • Preparation process of rubber PVC coated yarn

    CN118773788A

  • Corrosion-resistant PE cable and preparation process thereof

    CN118866442A